EFFECTIVENESS OF ACADEMIC ADMINISTRATION IN THE DIGITAL AGE OF EDUCATIONAL INSTITUTIONS UNDER SUPHANBURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Naklampa, Suwanunt; Boonphadung, Suttipong (Journal of Educational Review Faculty of Education in MCU, 2026)
The purposes of this research were to: 1) examine the level of effectiveness of academic administration in the digital era in schools under the Suphan Buri Primary Educational Service Area Office 2, and 2) compare the effectiveness of academic administration in the digital era among these schools based on school size. The study employed a qualitative research design. The sample group consisted of 302 participants selected through stratified random sampling without proportional allocation. The research instrument was a questionnaire with a reliability coefficient of 0.98. Data were analyzed using percentage, mean, and standard deviation, while the research hypotheses were tested using the t-test. The results of the research found that 1) the level of effectiveness of academic administration in the digital age of educational institutions Under the jurisdiction of the Suphanburi Primary Educational Service Area Office, Area 2, overall, each aspect has an average level at a high level. 2) Results of comparing the effectiveness of academic administration in the digital age of educational institutions. Under the jurisdiction of the Suphanburi Primary Educational Service Area Office, Area 2, classified by school size. It was found that there was no difference between small schools and medium and large schools.